Clinical Evaluation of the Effect of Implant-Supported and Implant Retained Distal Extension Removable Partial Dentures on the Supporting Structures - Kotb, Ragia Saad Mohamed; Gamal Ahmed Hassan, Ahmed; Mohamed Tolba M. Agamy, Emad; Fekry Mohamed, Gehan (Open Access Macedonian Journal of Medical Sciences, 2021)
Objective: To evaluate and compare the effect of implant supported versus implant retained removable partial denture restoring Kennedy's class I cases on the supporting structures by measuring modified gingival index and probing depth for abutment teeth and implants. Subjects and Methods: Twelve patients; who had Kennedy class I mandibular partially edentulous ridge extending distal to the first or second premolar, were selected from the outpatient clinic, Prosthodontics Department, Faculty of Dentistry, Minia University. The patients were classified into two equal groups; according to the implant superstructures either dome shaped abutment or ball and socket attachment. Each Patient of both groups had two implants in second molar position (one in each side) and received removable partial denture of the same design. Patients were followed up for one year clinically. Group I: Six patients received RPD supported by dome shaped short abutments. Group II six patients received RPD retained by ball and socket attachments. Results: Results revealed that, there was no statistically significant difference between the two groups regarding modified gingival index and probing depth around the abutment teeth and implant abutment. Conclusion: The use of dome shaped abutment or ball and O-ring attachment have the same effect on gingival index and probing depth around natural abutments and implants in Kennedy class I mandibular situations.